Design, iterative synthesis and structure of novel optically active trispiro-dendritic melamines incorporating 'open-chain' versus 'closed-chain' serinolic peripheral units. Issue 14 (31st July 2015) - Moldovan, Oana; Nagy, Iulia; Lameiras, Pedro; Antheaume, Cyril; Sacalis, Carmen; Darabantu, Mircea
Graphical abstract